SARS-CoV-2 RNA may rarely be present in a uterine cervix LBC sample at the asymptomatic early stage of COVID 19 disease - Ondič, Ondrej; Černá, Kateřina; Kinkorová-Luňáčková, Iva; Němcová, Jana; Mejchar, Bořivoj; Chytra, Jan; Bouda, Jiří (Cytopathology, 2021)
OBJECTIVE: Currently, it is thought that uterine cervix mucosal samples present a low risk of SARS-CoV-2 exposure. So far, there is no evidence of SARS-CoV-2 detection in Papanicolaou (Pap) smears. Nevertheless, clinicians could be exposed unaware to the coronavirus while performing and handling a Pap smear. We aimed to retrospectively evaluate the presence of SARS-CoV-2 RNA in cervical liquid-based cytology (LBC) samples in women who tested positive for a nasopharyngeal COVID-19 PCR test. METHODS: From our laboratory database, we identified patients with data on a cervical cancer screening LBC sample paired with a positive nasopharyngeal COVID-19 PCR test. Relevant LBC samples taken within an incubation period of 14 days and post-onset RNA shedding interval of 25 days were subsequently tested for SARS-CoV-2 RNA using RT-PCR tests. RESULTS: The study group consisted of 102 women. Of those, 23 LBC samples were tested. SARS-CoV-2 RNA was detected in one LBC sample from a 26-year-old asymptomatic woman taken six days before reporting headaches and knee arthralgia with a positive nasopharyngeal SARS-CoV-2 RT-PCR test. CONCLUSIONS: It is possible to detect SARS-CoV-2 RNA in cervical LBC samples at an early asymptomatic stage of COVID-19. In general, this finding is infrequent in asymptomatic women who tested SARS-CoV-2 positive within an incubation of 14 days and a post-onset RNA shedding period of 25 days. We fully support the current thinking that cervical LBC samples from asymptomatic women pose a low risk of SARS-CoV-2 exposure and can be handled in the frame of good microbiological practice and procedures.
Keywords: Humans; lidé středního věku; vaginální stěr; Female; dospělí; nádory děložního čípku; lidé; Adult; COVID-19; ženské pohlaví; Papanicolaou Test; Papanicolaouův test; Middle Aged; Retrospective Studies; testování na COVID-19 průkazem nukleové kyseliny; COVID-19 Nucleic Acid Testing; Uterine Cervical Neoplasms; retrospektivní studie; Vaginal Smears; SARS-CoV-2